(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2012)
The main morphometric parameters are identified for the 12 species of Chlamydomonas, which belong to the molecular Moewusinia clade, with 15 strains (including 12 authentic) as an example. Those parameters are assessed for the first time on the ground of slant culture as the criteria of the specific and intraspecific level within investigated clade. It is revealed that according to the criteria of the width of the cells within Moewusinia clade, selected strains can be divided into four groups which coincide with molecular - phylogenetic clusters with high bootstrap support. Within each of the group the average length of the cell is the distinguished feature of the specific level. The size of the cell is the base for identification of Moewusinia clade strains in the slant culture.